Staff Knowledge and Attitudes Towards COVID-19 New Biosafety Practices at a Brazilian Dental School - Ana Carolina Marques-Medeiros; Renata Castro Martins; Maria Elisa Souza e Silva; Ênio Lacerda Vilaça; Leandro Napier de Souza; Maria Auxiliadora Parreiras Martins; Ricardo Santiago Gomez; Mauro Henrique Nogueira Guimarães de Abreu (Association of Support to Oral Health Research (APESB), 2022)
Objective: To evaluate knowledge and attitudes towards biosafety recommendations during the COVID-19 pandemic at a Brazilian dental school. Material and Methods: A cross-sectional study was performed in 2020 with the clinical staff of a Brazilian dental school. The whole clinical staff was sent pre-tested self-administered online questionnaires about knowledge and attitudes towards the recommendations for biosafety in dental settings in the context of the COVID-19 pandemic. Descriptive statistical analyses were carried out for proportion calculation. Results: Disposable head covering caps, isolation gowns, and gloves were the most frequently reported personal protective equipment (PPE). The rates ranged from 52.9% to 88.5% for N95 respirators, from 68.6% to 92.6% for face shields, from 47.4% to 67.5% for conventional eye protection shields, and 45.1% to 77.4% for eye protection with solid side shields. Chlorhexidine gluconate was the most frequent mouthwash indicated before clinical dental care. The percentage of agreement to provide clinical care to patients with suspected COVID-19 varied from 23.5% to 50.0%. The percentage of respondents who agreed that bioaerosol-generating procedures should be avoided was higher than 74.5%. Less than 50% knew the correct sequence for doffing of PPE. Conclusion: This study revealed important gaps in knowledge and attitudes towards prevention and control measures against infection in dental environments in the context of COVID-19, indicating the need for improvements.